قواعد الترجيح في "تيسير التفسير" للشيخ امحمد بن يوسف اطفيش (ت: 1332ه/1914م) -دراسة تأصيلية تطبيقية- - دجال, عمر بن سعيد (جامعة أحمد دراية, 2017)
Keywords: Coran -- Commentaires -- 19e siècle

الصغائر من الذنوب عند الإباضية - علي, إلياس سعيد عجيلي (كلية العلوم الشرعية, 2017)
Keywords: Fiqh

مدنين دراسة في الجغرافيا الحضرية وجغرافية العلاقات - ضيف الله, الطاهر (كلية الآداب والعلوم الإنسانية, 2017)
Keywords: Djerba -- Gouvernorat

Evolution de l'architecture des coupoles en Tunisie aux époques médiévale et moderne - Ladhari, Aida (Faculté des Sciences Humaines et Sociales, 2017)
Keywords: Architecture -- Djerba; Ghuraba, mosquée al- (Houmt Souk, Djerba); Monuments -- Djerba

التعمير والعمران بجبل نفوسة في العصر الوسيط - الزواري, محمد (كلية الآداب والعلوم الإنسانية, 2017)
Keywords: Urbanisme -- Djebel Nefousa

المنهج الفقهي للشيخ الجناوني من خلال كتاب النكاح - أحمد, عيسى بن سعيد (كلية العلوم الشرعية, 2017)
Keywords: Jannāwunī, Yaḥyā b. al-Khayr; الأحكام (فقه إسلامي); الزواج (الشريعة الإسلامية)

شخصيات من نفوسه في القرن الرابع عشر الهجري: من 1882م إلى 1979 - إسماعيل, عبد العزيز علي (كلية العلوم الشرعية, 2017)
Keywords: Biographies -- Djebel Nefousa

الفقهيه عمرو بن رمضان التلاتي حياته و آثاره العلمية: حياته و آثاره العلمية - الصقال, أصيل بن بوعيش (كلية العلوم الشرعية, 2017)
Keywords: Biographies -- Djerba

ترجيحات الشيخ سعيد القنوبي في كتاب "الطوفان الجارف لكتائب البغي و العداون" - العبري, هلال بن خلف (كلية العلوم الشرعية, 2017)

الإمام السالمي و ترجيحاته (مشارق الأنوار أنموذجا) - البرواني, سيف بن سعيد (كلية العلوم الشرعية, 2017)

التوسل عند الإباضية - الجامودي, سعيد بن علي (كلية العلوم الشرعية, 2017)

موقف الشهرستاني من الإباضية نقدا و تحليلا - الصوافي, أحمد بن سعيد (كلية العلوم الشرعية, 2017)

الشيخ عبد الله حنبولة و جهودة الإصلاحية في مدينة زوارة - جرافة, إلياس سعيد عجيلي (كلية العلوم الشرعية, 2017)
Keywords: Réformisme -- Zouara

بنو إسماعيل ودورهم العلمي والحضاري ق: 11 هج / 17مـ ـ 14هج/20م - الإسماعيلي, سيف بن سليمان (كلية العلوم الشرعية, 2017)

أوضاع عمان السياسية خلال الفترة (280 - 442 هـ / 893 - 1050 م) - آل فنه, بلقيس بنت محمد بن سعيد (جامعة السلطان قابوس, 2017)

الحياة العلمية في عمان خلال الفترة (ق 6هـ/12 - ق 8هـ/14م) - الكلباني, نورة بنت سيف بن راشد (جامعة السلطان قابوس, 2017)
Keywords: Vie intellectuelle -- Oman -- 14e siècle

السياسة القضائية عند الإمام محمد بن عبدالله الخليلى ( ت : 1373 هـ / 1954 م ) : دراسة فقهية تحليلية - الكيومى, خلفان بن على بن خلفان (جامعة السلطان قابوس, 2017)

آل الرحيل ودورهم السياسي والفكري في عمان من القرن (2هـ / 7م - 4/ 10م) - النبهاني, بدرية بنت محمد بن شامس (جامعة السلطان قابوس, 2017)

رواة الجزئين الثالث والرابع من كتاب الترتيب للإمام أبي يعقوب الوارجلاني: دراسة توثيقية - الهنائي, عبدالله بن خلف بن محمد (جامعة السلطان قابوس, 2017)

الحكومة المحلية: عوامل البناء وحدود المشاركة جرادو، صفاقس، جربة - الأمين, سليمان (كلية العلوم الأنسانية والإجتماعية, 2017)

موقف الاباضية من الصحابة رضي الله عنهم من خلال كتاب الجواهر المنتقاة للبرادي - الشمري, منى غدير فهيد (الجامعة الإسلامية بالمدينة المنورة, 2017)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-

الموسيقى في البلاد التونسية قراءة في الوثيقة الموسيقية - الطرابلسي, فراس (المعهد العالى للموسيقى, 2017)

العلاقات الصفرية الإباضية في بلاد المغرب الإسلامي ما بين القرنين 2 - 4 هـ / 8 - 10 م - عبد الله, كريمة عازب (جامعة الوادي, 2017)
Keywords: Sufrisme

Câbir B. Zeyd ve İbaziyye içindeki rolü - Sülün, Cevat (Dicle Üniversitesi Sosyal Bilimler Enstitüsü, 2017)
Bu çalışmada, ibâzîler tarafından mezhebin fikri müessisi olarak kabul edilen Câbir b. Zeyd‘in hayatı ve fırka içindeki rolü ele alınmııtır. Arap âleminde Câbir b. Zeyd hakkında çok az sayıda müstakil çalışmalar vardır. Ülkemizde ise doğrudan Câbir b. Zeyd‘i konu alan müstakil bir çalışma yoktur. Tezimizin amacı Câbir b. Zeyd‘in hayatı, ilmi kişiliği ve fırka içerisindeki rolünü ortaya koymaktır. Tezimiz giriş, iki bölüm ve sonuçtan oluşmaktadır. “Câbir b. Zeyd” adını taşıyan tezimizin birinci bölümünde, Cabir‘in hayatı ve ilmi kiiiliği ele alındı. Bu bağlamda, Câbir b. Zeydi‗n doğumu, nesebi ve kişisel özellikleri üzerinde duruldu. ilmi şahsiyetini ortaya koyabilmek için, ilmî kişiliği, hocaları, talebeleri ve eserleri hakkında bilgi verildi. ibâzî kaynaklara bakıldığında, Cabir b. Zeyd islam ilimlerinin tek bir alanında mütehassıs bir bilgin olmaktan ziyade tefsir, hadis, fıkıh ve kelam alanlarında temayüz eden çok yönlü bir bilgindir. ibâzî kaynaklara dayanılarak, Cabir b. Zeyd‘in Bedir ehlinden yetmiş kişi ile görüştüğü ve onlardan ders aldığı belirtildi. Bu bölümde İslam'ın erken dönemlerinde telif edilen ilk kaynaklardan sayılan Câbir b. Zeyd‘in Divân adlı eseri ve Divan üzerine yapılan çalışmalar hakkında bilgi verildi. Câbir b. Zeyd‘in ilmi mirasıyla alakalı yapılan çalışmalar araştırıldı. İkinci Bölüm, Câbir b. Zeyd‘in fırka içerisindeki rolüne ayrılmıştır. Bu bölümde öncelikle, Cabir‘in sosyal hayatı ve Emevî idaresiyle olan münasebeti irdelenmiştir. Cabir b. Zeyd‘in İbâziyye ile olan ilişkisi Sünni ve İbâzî kaynaklarda farklı şekilde ele alınmaktadır. Bazı sünni kaynaklar Cabir b. Zeyd‘in İbâziyye ile olan iliikisini inkâr ederken İbâzî kaynaklar onu fırkanın fikri müessisi olarak ele almaktadır. Bu bölümde konuyla ilgili ileri sürülen süpekülasyonlar sünni ve Gbâzî kaynaklar üzerinden değerlendirilmiştir. Cabir b. Zeyd ile ilgili tartışmalarda yeri geldikçe mektuplarına da yer verilmiştir. Sonuç kısmında Cabir b. Zeyd ve onun fırka içindeki rolü hakkında İbâzî ve sünni kaynaklar tarafından verilen bilgilerin genel bir değerlendirmesi yapılmıştır. Anahtar Kelimeler Câbir b. Zeyd, Abdullah b. Gbâz, Gbâzîlik, Ka‘ade, Nehrevân.

Er-Rebî' B. Habîb ve El-Câmiu's-Sahîh adlı eseri / Rabî' B. Habîb's work titled Al-Jâmi' Al-Sahîh - Özdemir, Ahmet (Dicle Üniversitesi Sosyal Bilimler Enstitüsü, 2017)
According to Ibâdiyyah, Rabî' b. Habîb's work titled al-Jâmi' al-Sahîh is of the hadith sources belonging to second century hijri. Rabî is one of the most important muhaddiths of Ibadiyyah. His work is also the most acknowledged hadith source in this sect and even it has become famous as the most authentic religious text after the Holy Quran. However, among the other Islamic sects except Ibâdîs, the work is almost unknown. This thesis contains the topics such as the history of the work until today, its attribution to the author, the value of its content in terms of sihhah (authentication), the comparison of the work with the other hadith sources in terms of form and text, the reflection of the scientific and intellectual movements of the period on the work and the correctness of the claims of Ibâdîs on the sihhah of the work. In the introduction of this study, information about the importance, method and sources of the thesis as well as about Ibâdiyyah sect in general is provided. In the first section, Rabî 'b. Habîb's biography and scientific personality and in the second one the characteristics of the work in terms of narration are discussed. In the third chapter, the work is analyzed and evaluated in terms of dirayah (cognition). In the conclusion, the findings reached in the thesis are reported. Some of the results of the study are as follows: the attribution of the work to the author is even discussed issue today but the work has an important similarity with other hadith sources in terms of form and content. Most of the narrations in the work are also included in the famous hadith corpus of the second and third centuries. Like the other hadith sources, Rabî''s al-Jâmi' also contains authentic, weak and even fabricated narrations, even if Ibâdîs disagree with that. Al-Jâmi 'of Rabî', used only by Ibadîs until now is worthy to be used as a source in scientific researches even though there are its some significant shortcomings. Key Words: Ibâdiyyah, Hadith, Rabî' b. Habîb, al-Jâmi', Jâbir b. Zayd, Sanad, Matn.
Keywords: Hadith -- Ibadisme

Doğu Arabistan'a İslâmiyet'in girişi - Aslandoğdu, Elif Kübra (Uludağ Üniversitesi, 2017)
Bu çalışmada Doğu Arabistan sınırları içerisinde ele aldığımız Umân, Yemâne ve Bahreyn bölgelerinin İslâmiyet'le olan münasebetleri incelenmiştir. Üç bölüm halinde ele alınan tezin ilk bölümü İslâmiyet öncesi döneme, ikinci ve üçüncü bölümleri ise İslâmiyet'in kabulü ve irtidât hadiselerine ayrılmıştır. Sâsânî devletinin denetimi altında olan bu bölgelerin yöneticileri Hz. Peygamber'in davetine olumlu şekilde karşılık vermişler, onlarla birlikte bölge halkından Araplar ve Farslılaların bir kısmı İslâm'ı kabul etmişlerdir. Çeşitli kabilelerden temsilcilerin Hz. Peygamber'le görüşmek üzere Medine'ye geldikleri heyetler yılında da bu bölgelerden heyetler gelmiş ve Müslüman olarak geri dönmüşlerdir. Fakat bu durum çok uzun sürmemiş, Hz. Peygamber'in hayatının son dönemlerinden başlayan isyan ve dinden dönme hadiseleri vuku bulmuştur. Birçok nedeni bulunmakla birlikte, genel olarak siyasî faktörlerin sebep olduğu bu kaos ortamı Hz. Ebû Bekir'in kararlı tutumuyla kontrol altına alınmış ve bu bölgeler tekrar Medine yönetiminin otoritesi bağlanmıştır.

الفعالية التنضيمية في المؤسسة الوقفية دراسة مونوغرافية حالة: مؤسسة الغفران الخيرية زلاية غرداية الجزائر - بهون علي, إباض (جامعة أمين العقال الحاج موسى آق أخموك, 2017)
Keywords: Waqf (fondations) -- Mzab

امحمد بن يوسف اطفيش وجهوده البلاغية مع تحقيق كتابه ربيع البديع في علم البديع - لقدي, محمد (جامعة الحاج لخضر, 2017)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914)

معهد الحياة بالقرارة (ميزاب) ودوره الإصلاحي 1925-1945 - قرون, حنان; شرحة, فريدة (جامعة محمد بوضياف, 2017)
Keywords: Réformisme -- Mzab

تحقيق كتاب : رفع التراخي في مختصر الشماخي للشيخ عمرو بن رمضان التلاتي الإباضي (ت 1188هـ) من بداية الباب الرابع في الخاص والعام إلى نهاية الكتاب - الخروصي, المعتصم بن خالد بن سليمان (جامعة الأزهر, 2017)

الشيخ حمو بن عمر فخار وجهوده في التربية والإصلاح بمزاب 1365-1426هـ/1947-2005م - حريز, صالح (جامعة غرداية, 2017)
Keywords: Réformisme -- Mzab

النشاط الزراعي ونظام الري في واحة القرارة ما بين 1333-1371هـ/1915-1952م من خلال الوثائق الأرشيفية سجلات قياد القرارة - ويرو, يحيى إبراهيم (جامعة غرداية, 2017)
Keywords: Agriculture -- Mzab

صورة الشخصية الفرنسية في شعر مفدي زكرياء - البار, منيرة (جامعة محمد خيضر, 2017)
Keywords: Poésie -- Mzab

جماليات التلقي في ديوان اللهب المقدس - ابن التومي, نوال (جامعة محمد بوضياف, 2017)
Keywords: Poésie -- Mzab

قصور ورقلة الأثرية بين التاريخ والحضارة روبورتاج مصور حول القصور الأثرية والحضارية بولاية ورقلة دراسة حول القصر العتيق وقصر الشط - بن محسن, محمد وثیق; الأدغم, صفاء (جامعة قاصدي مرباح, 2017)
Keywords: Architecture -- Ouargla

Les transformations urbaines récentes d'une ville coloniale du Sénégal: Thiès - Gueye, Serigne Ahmadou (Université Paris 8, 2017)

الاجتهاد المقصدي عند إبراهيم بن عمر بيوض (1313-1401هـ) من خلال كتاب الفتاوى: دراسة تأصيلية تطبيقية - كركاشة, مريم علي (جمعية الإصلاح, 2017)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981); Fatwas -- Mzab -- 20e siècle; Ijtihad -- Mzab -- 20e siècle

Transformations spatiales et dynamiques socio-environnementales de l’oasis de Ouargla (Sahara algérien). Une analyse des perspectives de développement. - Salhi, Abdelkader (Aix-Marseille université, 2017)

Etude des Propriétés Hydriques des Sols Alluviaux de la Région du M'zab: Cas de L'oasis de Guerrara - Boucetta, Malika (جامعة قاصدي مرباح, 2017)
Keywords: Irrigation -- Mzab

La mise en tourisme du patrimoine culturel saharien - cas d'étude: la vallée du M'Zab - Chaoui, Lynda (Université du Québec, 2017)
Keywords: Tourisme -- Mzab

صالح بن يوسف والحماية الفرنسية على تونس - مرسالم, أم الشيخ; مايني, جازية (جامعة الجيلالي بونعامة خميس, 2017)
Keywords: Ben Youssef, Salah 1907-1961

Étude ethnographique des jeux traditionnels dans la region du M’zab - Bekai, Ismail (Université de Hassiba Benbouali, 2017)
Keywords: Jeux -- Mzab

مسألة أسماء الله عند الشيخ الشماخي - المليان, محمد بن علي (جامعة الزيتونة, 2017)

صفات الله بين التأويل والتفويض عند إباضية المغرب: القطب أطفيش نموذجا - بن جماعة, راضية (جامعة الزيتونة, 2017)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914)

The Ottoman Province of Tripoli (Libya) in German Politics between 1884 and 1918 - Ghafal, Suaad Mohamed Omar Al (Freien Universität Berlin, 2017)

Ṣālaḥ b. Yūsuf wa’l-ḥimāya al-Faransiyya ʿalā Tūnis - Umm al-Shaykh, Marslām; Māynī, Jāziyya (Jāmiʿat al-Jīlānī Būnʿāma Khamīs, 2017)
Keywords: Ben Youssef, Salah 1907-1961

Creating an enabling environment in private higher education in Oman - Balushi, Ali Hamdan al- (University of Southampton, 2017)
This research undertakes a critical evaluation and analysis of the leadership style at higher education institutions in Oman and determines whether the direction it takes is in strict conformity with creating an enabling environment there. To address this, Saxena’s framework on creating an enabling environment in higher education is used as a foundation, along with the theoretical concepts of transformational leadership to explore the role of heads of higher education institutions in creating an enabling environment. Hence, the major question examined in this thesis is: “To what extent do presidents and deans create an enabling environment and act as transformational leaders at private higher education institutions in Oman?” The research employed a mixed method design in which data were collected through a combination of semi-structured interviews with presidents, deans, officials, and recent graduates. A survey of lecturers, full-time employees, and students was also undertaken to seek their views. The target sample in the main research was drawn from six private universities and colleges and selected public Ministries. In line with the theoretical structure, the findings of the research show the higher education environment in Oman to be an area of concern. The findings highlight four gaps, which also fall in line with the four components introduced by Saxena. The first gap is between the higher education institutions and industry; the second gap relates to empowerment among staff, management, governance and authorities; the third gap is between physical environment and facilities; and the fourth gap is between research and teaching. The findings recommend a leadership framework to provide necessary guidelines for creating an enabling environment. The research opens avenues for upcoming researchers who would add more to the previously achieved goals so that the sustenance offered by lifelong learning may also be perpetuated in the years to come.
Keywords: Enseignement -- Oman

المسكوكات الإسلامية المضروبة في عُمان منذ بداية القرن الثالث الهجري - التاسع الميلادي وحتى نهاية القرن الخامس الهجري - الحادي عشر الميلادي في ضوء مجموعات لم يسبق نشرها - الفضلي, إبراهيم بن أحمد بن محمد (جامعة المنصورة, 2017)

قضية التكفير وضوابطها بين الاباضية و الامامية فى ضوء عقيدة أهل السنة و الجماعة - فهد, مبارك عبد الله (جامعة القاهرة, 2017)
فهذه دراسة علمية اتجهت إلى تناول قضية من أخطر القضايا التي تهم المسلمين، والتي أثرت عليهم في ماضيهم وما زالت تؤثر في حاضرهم، وسيظل لها ذلك التأثير إلى أن يرث الله الأرض ومن عليها. يدور بحثنا هذا حول مسألة التكفير وضوابطها وأصول الدين عند فرقتين من الفرق الكلامية التي ظهرت في مرحلة مبكرة من التاريخ الإسلامي. ويأتي هذا البحث تحت العنوان الآتي: «قضية التكفير وضوابطها بين الإباضية والإمامية وأهل السنة والجماعة: دراسة مقارنة».
Keywords: Religions comparées -- Ibadisme -- Acharisme

المنهج العلمي عند متكلمي الإباضية في تفسير آيات العقيدة خلال القرن السادس الهجري - الجهوري, راشد بن حميد (جامعة السلطان قابوس, 2017)

ضوابط الصحة و الفساد في فقه العبادات عند الإباضية :‏ ‏دراسة أصولية فقهية مقارنة - بابزيز, داود بن عمر بن موسى (جامعة السلطان قابوس, 2017)
Keywords: Fiqh

إعمال العقل في المسائل العقدية و ضوابطه عند الإباضية :‏ ‏دراسة تأصيلية من النشأة و حتى القرن السادس الهجري - العامري, أحمد بن سعيد (جامعة السلطان قابوس, 2017)

الجزء الثالث من الكتاب الأول وحتى الكتاب الثاني من كتاب الاستقامة للعلامة أبي سعيد الكدمي :‏ ‏دراسة و تحقيق - السابقية, سامية بنت حمد (جامعة السلطان قابوس, 2017)

اجتهادات الإمام محمد بن عبد الله الخليلي و أصولها الشرعية :‏ ‏دراسة تأصيلية - الخروصي, أحمد بن سالم (جامعة السلطان قابوس, 2017)
Keywords: Fiqh; Fiqh -- Oman -- 19e siècle; Ijtihad -- Oman -- 19e siècle

اختلاف دلالة المصطلح العقدي بين الفرق الإسلامية :‏ ‏دراسة مقارنة: الإباضية مقارنة بالمعتزلة و أهل الحديث و الأشاعرة و الماتريدية - القلهاتي, راشد بن مبارك (جامعة السلطان قابوس, 2017)

السياسة القضائية عند الإمام محمد بن عبد الله الخليلي (ت 1373هـ/1954م) :‏ ‏دراسة فقهية تحليلية - الكيومي, خلفان بن علي (جامعة السلطان قابوس, 2017)
Keywords: Fiqh

الوعي بالمكان في السير الإباضية ببلاد المغرب كتاب السير لأبي الربيع عبد السلام الوسياني نموذجا - فارس, محمد (كلية العلوم الانسانية والاجتماعية, 2017)
Keywords: Prosopographie -- Afrique du Nord

قصر بن عياد بجزيرة جربة: مشروع للتوظيف و الاستغلال - بن براهيم, مروان (المعهد العالي لمهن التراث, 2017)
Keywords: Architecture -- Djerba

تنظيم المجال والتوطين والتعمير بجزيرة جربة في العهد الوسيط أطروحة الدكتوراه في علوم التراث - بربو, المنصف (كلية العلوم الانسانية والاجتماعية, 2017)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Abu Muhammad Kammus, mosquée (Hachene, Djerba); Abu Smayil, mosquée (Mezrane, Djerba); Abu Zakariyya Fasil, mosquée (Bani Bandou, Djerba); Ammi Yathi, mosquée (Fahmine, Djerba); Ben Biyan, mosquée (Majmaj, Djerba); Bin Ya'lâ, mosquée (Erriadh, Djerba); Bin Yakhlaf, mosquée (Guechaine, Djerba); Bûkhtîr, mosquée (Taghdimes, Djerba); Bûlaymân, Mosquée (Cedghiane, Djerba); Ghuraba, mosquée al- (Houmt Souk, Djerba); Hâra, mosquée al- (Sedouikech, Djerba); Jaddi Isa, mosquée (Robbana, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Monuments -- Djerba; Mthaniya, mosquée al- (Ajim, Djerba); Mughzal, mosquée (Beni Maaguel, djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Sidi Abd Allah, mosquée (Mezrane, Djerba); Sidi Garus, mosquée (Haddada, Djerba); Sidi Khalifa, mosquée (Houmt Arbah, Djerba); Sidi Sabbaḥ, mosquée (Tezdaine, Djerba); Sidi Salama, mosquée (Erriadh, Djerba); Sidi Salih, mosquée (Bani Bandou, Djerba); Sidi Waḥlan, mosquée (Haddada, Djerba); Sidi Zakri, mosquée (Mezraya, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tghazwisan, mosquée (Mezrane, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîfarrûjîn, mosquée (Oualagh, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba); Walḥī, mosquée (Oued Zbib, Djerba)

التفكير النحوى عند الشيخ التغزويسنى الجربى مع تحقيق " شرح متن الأجرومية " - حاج أمحمد, عيسى (جامعة اليرموك, 2017)

الفكر العقدي عند الشيخ أبي المنذر بشير بن محمد بن محبوب الرحيلي وأثره القيمي والحضاري - الرحيلية, الغالية بنت محمد (جامعة السلطان قابوس, 2017)

الأبنية الصرفية ودلالاتها فى ديوان شعر الخوارج - الشبول, نبيل موسى محمد (جامعة اليرموك, 2017)
Keywords: Poésie kharijite

آراء الخوارج الإباضية والأزارقة والصفرية والنجدات الاعتقادية وأثرهم في الفكر الإسلامي المعاصر (داعش): دراسة مقارنة - بلغول, عمرو بن أحمد (جامعة المدينة العالميه, 2017)
Keywords: Kharijisme

The Khawārij and religious identity formation in early Islam - Thomson, Rodney L. (California State University, 2017)
The problems inherent to the sources for early Islam continue to challenge scholars when it comes to making positivist statements regarding the formation of early Muslim identity. Specialists have long recognized that the polemical struggles for orthodoxy and legitimacy in the Abbasid period plague the akhbār and ḥadīth. This problem is particularly acute for the Khawārij, the first recognized sectarian division in Islam. The present author examines the sources using social identity theory and the analytical tools of the Biblical text critic, both of which find fruitful application to the early Muslim sources. Further support derives from an understanding of the Late Antique and tribal environments prevalent in the first Hijri centuries. Through careful application of these tools, the present author deconstructs the Khārijī master narrative to separate later inventions or redactions from those more likely to represent the sectarians as they actually existed. Akhbār, poetry, and apologetic literature ascribed to the Khawārij are then analyzed to show how the sectarians’ early self-identity did not stray far from its pre-Islamic heritage, but evolved over time to include detailed religious justification. The author concludes with the suggestion of a new Khārijī narrative in which the sect's dissent stemmed principally from complaints fully coherent with the Arabian tribal milieu, to which members only later developed doctrine to legitimate their separatism.
Keywords: Kharijisme

Urbanisation, société et territoires Midoun (Djerba) - Ben Jebara Boussaada, Sarra (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2017)
Keywords: Architecture -- Djerba

Migrations, territorialités, dynamiques interculturelles: L'exemple de la minorité mozabite - Abderrezek, Kaouther (Université Clermont Auvergne, 2017)
À l’heure où la mobilité est accrue et les valeurs culturelles se dirigent de plus en plus vers l’unification, il nous a paru important d’observer les migrations des groupes diasporiques à fortes valeurs identitaires et d’analyser leurs territorialités et leurs dynamiques interculturelles. Ce travail ambitionne donc d’amorcer une étude géographique du phénomène migratoire diasporique. Il porte le regard sur l’analyse de l’espace migratoire qui se forme entre le lieu d’origine du groupe minoritaire et ses pôles d’installation avec un exemple précis sur la minorité ethnolinguistique et religieuse des Mozabites algériens qui migrent et s’approprient différents pôles dans le contexte interne et international. Le choix d’analyser plusieurs pôles d’installation (El-Eulma en Algérie, Marseille et Lille en France) et de mettre en rapport la migration interne et la migration internationale de ce groupe, a permis d’évaluer l’influence des différents facteurs sur la conception des phénomènes migratoires diasporiques. Il a aussi éclairé sur la manière dont l’appartenance identitaire est une variable que le groupe diasporique sollicite fortement pour former son espace et son système migratoire At a time when mobility is increasing and cultural values are moving more and more towards unification, it was important to observe the migration of diasporic groups with strong identity values and to analyze their territorialities and intercultural dynamics. This work aims to initiate a geographical study of the diasporic migratory phenomenon. It is concerned with the analysis of the migratory space between the original place of the minority group and its poles of settlement with the specific example of the ethnolinguistic and religious minority of the Algerian Mozabites who migrate and appropriate different clusters in the internal and international context. The choice of analyzing several installation clusters (El-Eulma in Algeria, Marseille and Lille in France) and to compare the internal migration with the international migration of this group, made it possible to evaluate the influence of the different factors on the design of diasporic migratory phenomena. It also enlightened on how identity belonging is a variable solicited by the diasporic group to form its space and its migratory system
Keywords: Emigration -- Mzab -- Algérie

Architecture des ksour de la Vallée de Mzab: Essai d'histoire, de sémiotique et de médiation - Si Amer, Aziza Nesrine (Université de Tours, 2017)
Ce travail porte sur l’histoire médiévale, l’architecture et le patrimoine de la vallée du Mzab, sa sémiotique et sa médiation culturelle. Il s’agit d’un essai d’analyse, de compréhension et d’interprétation de la vallée du Mzab, visant à sa restitution et à sa valorisation culturelle, envisagée à travers le mouvement de réforme religieuse, architecturale et sociale qu'a connu cette minorité algérienne. Ce travail a pour but de comprendre comment par cette réforme historiographique la minorité berbérophone et confessionnelle mozabite a trouvé les réponses aux changements suscités par son intégration progressive à la nation algérienne, à la société et à l'espace architectural et urbain This work focuses on medieval history, architecture and heritage of the Mzab Valley, its semiotics and its cultural mediations. It is an attempt to analyze, understand and interpret the Mzab valley, aiming at its restitution and its cultural valorization. Considering, this through, the movement of religious and social reforms experienced by this Algerian minority. The purpose of this work is to understand how, through this historiographic reform, the Mozabite Berber-speaking and denominational minority found the answers to the changes triggered by its progressive integration with the Algerian nation, society and space.
Keywords: Architecture -- Mzab

Recherches sur la présence ottomane et espagnole sur l’île de Ğirba/Djerba à la lumière des témoignages archéologiques - Msellem, Zied (Faculté des Sciences Humaines et Sociales de Tunis, 2017)
L’objectif principal de cette étude tend à classer les différents témoignages d’occupation Espagnole et Ottomane sur l’île de Ğirba ainsi faire un recoupement des données historiques et archéologiques pour faire éclairer cette épisode de l'histoire de l’île
Keywords: Archéologie -- Djerba